Relationships between tsetse challenge and trypanosome prevalence in trypanotolerant and susceptible cattle - Leak, S.G.A.; Colardelle, C.; Coulibaly, L.; Dumont, P.; Feron, A.; Hecker, P.; D'Ieteren, G.D.M.; Jeannin, P.; Minengu, M.; Minja, S.; Mulatu, W.; Nankodaba, G.; et al. (1990)
Reports results of a study on the relationships between tsetse challenge and trypanosome prevalence in trypanotolerant and susceptible breeds of cattle. Presents data on tsetse challenge and trypanosome prevalence in N'Dama and Zebu cattle in Zaire, Gabon, Ethiopia and Cote d'Ivoire.